1997
DOI: 10.1007/bf01291890
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine-GABAA receptor complex ligands in two models of anxiety

Abstract: In the present study, the actions of several compounds with different intrinsic activities and BDZ receptor selectivity were examined in two well established animal models of anxiety: the open field test (OFT) and Vogel's punished drinking text (VT). Full agonists at the BDZ GABAA receptor (midazolam and diazepam) showed anxiolytic-like effects in both tests; however, the doses necessary to disinhibit animal behavior controlled by fear were higher in the VT than in the OFT. None of the partial BDZ receptor ago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
21
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 21 publications
6
21
0
Order By: Relevance
“…The activity of indiplon in the Vogel test is consistent with that observed for both benzodiazepine and nonbenzodiazepine ligands in this, and other, conflict paradigms (Gardner and Piper, 1982;Martin et al, 1993;Nazar et al, 1997;Griebel et al, 1998) and may indicate that the compound has anxiolytic activity. However, in the mouse open field test, where the anxiolytic effects of benzodiazepine ligands are also apparent (Crawley, 1985), indiplon showed no increase in center time, but a decrease in this parameter and in total horizontal activity.…”
Section: In Vivo Pharmacology Of Indiplon 555supporting
confidence: 64%
See 1 more Smart Citation
“…The activity of indiplon in the Vogel test is consistent with that observed for both benzodiazepine and nonbenzodiazepine ligands in this, and other, conflict paradigms (Gardner and Piper, 1982;Martin et al, 1993;Nazar et al, 1997;Griebel et al, 1998) and may indicate that the compound has anxiolytic activity. However, in the mouse open field test, where the anxiolytic effects of benzodiazepine ligands are also apparent (Crawley, 1985), indiplon showed no increase in center time, but a decrease in this parameter and in total horizontal activity.…”
Section: In Vivo Pharmacology Of Indiplon 555supporting
confidence: 64%
“…Similar observations have been made previously in conflict versus ethologically derived tests comparing different benzodiazepine site ligands. Thus, "nonbenzodiazepine" agonists with selectivity toward GABA A receptors containing ␣1 subunits, including zolpidem and zaleplon, have a different profile to benzodiazepines such as diazepam and clorazepate (Griebel et al, 1996a(Griebel et al, ,b,c, 1998Nazar et al, 1997). Consistently, zolpidem and zaleplon show "anxiolytic" effects in conflict procedures, and anxiolytic activity is weak or absent in measures such as the open field test, light-dark box, and elevated plus maze.…”
Section: In Vivo Pharmacology Of Indiplon 555mentioning
confidence: 77%
“…10,11 Through the use of an F2 population derived from two inbred rat strains that differ for several anxietyrelated behaviors, Lewis (LEW) and Spontaneously Hypertensive rats (SHR), 12,13 a locus on rat chromosome 4 was found to affect locomotion in the central area of an open field (OF), 14 a putative index of experimental anxiety. 4,[15][16][17][18] The behavioral effects of this QTL, named Ofil1, were confirmed and extended through the use of recombinant lines derived from LEW and SHR rats, 19,20 suggesting that this genome region harbors one or more genes influencing anxietyrelated behaviors and alcohol consumption.…”
Section: Introductionmentioning
confidence: 97%
“…The in vitro studies showed ELB139 to be a low-affinity, partial agonist at the benzodiazepine binding site. Its IC 50 for the inhibition of specific [ 3 H]flunitrazepam binding was about 150 times higher than that of diazepam (Costa and Guidotti, 1996;Nazar et al, 1997;Dubinsky et al, 2002). Electrophysiological experiments in hippocampal neurons characterize the compound as a partial agonist because the potentiation of GABA-induced currents did not reach the potentiation obtained with diazepam, even after administration of 100 M, a dose approximately 95-fold higher than the IC 50 .…”
Section: Discussionmentioning
confidence: 99%